Neglected Ureteropelvic Junction Obstruction Leading to Giant Hydronephrosis: A Case Report and Review of Literature - Sadeghi Ardakani , Fatemeh; Samady Khanghah, Ali; Sonei, Mahdi; Sadeghi Ardakani , Mahta; Atqiaee, Khashayar; Ebrahimi Saraj, Gholamreza (Iranian Journal of Pediatric Surgery, 2025)
Giant hydronephrosis (GH) is an uncommon urological disease, and ureteropelvic junction obstruction (UPJO) is counted as one of the most common etiologies among children. This report presents a giant hydronephrosis resulting from a neglected complication of ureteropelvic junction obstruction in a 2.5-year-old girl with a history of gross hematuria and abdominal distention who underwent nephrectomy. A kidney that constitutes more than 1.6% of the overall body weight is counted as a giant hydronephrotic kidney. The possible differential diagnoses may include ovarian, mesenteric, pancreatic, and adrenal cysts, extra-renal tumors, Echinococcal cysts of the liver, non-renal retroperitoneal cysts, tuberculous peritonitis, and ascites. Due to the possibility of pyelonephritis, sepsis, and shock, paracentesis is not recommended in these cases. Ultrasonography is the primary modality employed for distinguishing the diagnoses mentioned above. Our survey of the pediatric population revealed that aside from UPJO, the most common anomalies were renal system duplication. Care for patients with GH is tailored to each individual, with significant differences between children and adults.